Evaluación técnica a escala laboratorio de un fluido de perforación base agua utilizando nanopartículas de lm-200 para la inhibición de Lutitas en el campo Castilla de Ecopetrol S.A (2018)
Filtrate losses are a critical issue during drilling operations that can lead to stuck pipes and mechanical instability and therefore an increase in costs. This work evaluates the use of bentonite nanoparticles, in order to improve rheological and filtration properties of a water-based drilling fluid used in Campo Castilla, operated by Ecopetrol S.A in Colombian Llanos Orientales basin.